Is the Association of South East Asian Nations (ASEAN) too Diverse for Effective Cooperation? - Vongsinsirikul, Suwat; Dautrey, Jean (KASEM BUNDIT JOURNAL, 2015)
Abstract The Association of Southeast Asian Nations (ASEAN) is hardly a household name, including in its own yard. Knowledge of the trading bloc and upcoming ASEAN Economic Community (AEC) remains essentially limited to scholars, government agencies, and large organizations, with many people - including many AEC stakeholders - still largely unaware of its existence. This knowledge deficit, however, does not reflect ASEAN’s increasing international stature and role in the Asia-Pacific rim and beyond. The purpose of this article is to introduce ASEAN and the Southeast Asian region and discuss whether the political, economic, and cultural diversity that characterizes it is an impediment to effective cooperation among its ten members in light of the upcoming integration at the end of 2015. While achieving unity may seem to be a tall order, this paper argues that the Association is less fragmented than it may appear to be due in no small part to the so-called ‘ASEAN Way’ and a recognized sense of benefits the ASEAN confers on its members.